A Systematic Review of ADHD Knowledge Measures and Their Psychometric Support. (20th February 2023) - Golson, Megan E; Brunson McClain, Maryellen; Ha, Jennifer; Stigler, Renae; Bera, Jac'lyn; Kieffer, Kaelah E B; Gibson, Abigail
Abstract: Objective: Attention-deficit/hyperactivity disorder (ADHD) knowledge is associated with reduced stigma, earlier identification, and increased intervention access. Several ADHD knowledge measures have emerged. However, the psychometric quality of these measures varies wildly, and a review of the current psychometric support for ADHD knowledge measures is lacking. Methods: The current study is a systematic review of ADHD knowledge measures for the reported psychometric support and the populations in which they are validated. The databases PsycINFO, ERIC, and PubMed were searched using PRISMA guidelines for peer-reviewed publications using a direct ADHD knowledge measure for original data collection. An ancestral search and the inclusion of dissertations were used to reduce potential publication bias. Included articles were coded for psychometric support, population of interest, and validation sample characteristics. Results: A total of 163 articles were identified, including a total of 96 ADHD knowledge measures. The majority of measures (71.8%) did not include adequate psychometric evidence to constitute an evidence-based measure. Within that, approximately a third of ADHD knowledge measures were not accompanied by any psychometric support. Many measures are designed for and validated in only one population. Most studies did not report racial and ethnic validation sample composition; among those that did, there is a lack of diversity. Conclusions: The lack of psychometric evidence for ADHD knowledge measures calls into question the current literature regarding ADHD knowledge, particularly related to racially and ethnically minoritized respondents with whom few measures have been validated. Implications for researchers and clinicians selecting an ADHD knowledge measure are discussed.